Karakteristik Kombucha dengan Penambahan Ekstrak Kayu Manis (Cinnamomum burmannii) dan Kayu Secang (Caesalpinia sappan) pada Proses Fermentasi Sekunder - Wahyudi, Ikwan; Lisdiana, Lisdiana; Astuti, Budi (Universitas Trunojoyo Madura, 2023)
This study aims to determine the characteristics of kombucha produced from a secondary fermentation process with the addition of extracts of cinnamon (Cinnamomum burmannii) and secang wood (Caesalpinia sappan). The study used a RAK design with 2-factor treatments and 4 replications. Treatment factors included the addition of ingredients (control, cinnamon, and secang wood) and secondary fermentation time (24, 48, and 72 hours). Characteristics observed include analysis of pH, density, and color (Lab). The results showed that there were significant differences in the pH value, density, and color due to the various treatments of adding ingredients. The pH value and density of kombucha did not differ significantly due to the variation in secondary fermentation time, but there were significant differences in the color of kombucha based on the secondary fermentation time.